'What do these words mean?': A qualitative approach to explore oral health literacy in Vietnamese immigrant mothers in Australia. (May 2014) - Arora, Amit; Nguyen, Deon; Do, Quang Vinh; Nguyen, Bao; Hilton, Glen; Do, Loc Giang; Bhole, Sameer
Objective: This study, nested within a large cohort study, sought to explore how well Vietnamese mothers with pre-school children understood the dental health education material commonly available in New South Wales, Australia. Design: Qualitative research. Setting: Home-based interviews. Method: Vietnamese-speaking mothers ( n = 24) with young children were provided with two dental leaflets which gave advice on health behaviours in English and Vietnamese for comparison. Interviews were recorded, transcribed verbatim and analysed using a thematic coding. Results: Mothers generally reported that the English leaflets were difficult to read due to their lower levels of English literacy skills. Although the mothers preferred leaflets in their native language, they noted that it did not completely reflect the Vietnamese culture. Mothers recommended pictorial presentations for immigrants to improve understanding. Conclusions: The consistency of our findings suggest that health education leaflets should be provided to parents in their first language with use of illustrations to improve understanding, and that producers of health education leaflets should consider cultural differences in translation.